(untitled) (Journal of Face Aesthetics, 2020)
A gummy smile is an excessive exposure of the gums while smiling. There are four types: anterior- excessive gum exposure from canine to canine, posterior — excessive gum exposure in the lateral segment, mixed — combining the anterior and posterior components, and asymmetrical — with a disproportion between the right and left side. The causes of gingival smile include: skeletal defect, delayed passive tooth eruption, nasal septal dysplasia, and excessive muscle activity. A simple, fast and minimally invasive method of gummy smile therapy caused by excessive muscle activity is the supply of botulinum toxin type A to the muscles responsible for a given type of smile. A favorable aesthetic effect can be achieved with a good knowledge of application sites and individually selected doses. When determining the dose, which is described in the literature between 2 IU and 10 IU onabotulin per page, researchers take into account not only the type of corrected smile, the number of puncture points, but also gender and age of the patient.